2017
DOI: 10.1038/nchem.2713
|View full text |Cite
|
Sign up to set email alerts
|

Engineering live cell surfaces with functional polymers via cytocompatible controlled radical polymerization

Abstract: The capability to graft synthetic polymers onto the surfaces of live cells offers the potential to manipulate and control their phenotype and underlying cellular processes. Conventional grafting-to strategies for conjugating preformed polymers to cell surfaces are limited by low polymer grafting efficiency. Here we report an alternative grafting-from strategy for directly engineering the surfaces of live yeast and mammalian cells through cell surface-initiated controlled radical polymerization. By developing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
389
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(393 citation statements)
references
References 55 publications
3
389
0
1
Order By: Relevance
“…To elicit if the P(PEGA) block remained at the particle surface, we used a PEG‐selective aggregation assay, based on the well‐known property of PEG as a tannin‐binding agent . This operates on a similar basis to lectin‐glycopolymer assays, where addition of an agent which can bind multiple substrates (nanoparticles, polymers, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…To elicit if the P(PEGA) block remained at the particle surface, we used a PEG‐selective aggregation assay, based on the well‐known property of PEG as a tannin‐binding agent . This operates on a similar basis to lectin‐glycopolymer assays, where addition of an agent which can bind multiple substrates (nanoparticles, polymers, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…[16,[24][25][26][27][28] As specific examples, considering the activity of PheoA (Figure 1a) and ZnTPP (Figure 1b) with respect to a set of six RAFT agents which comprises dithiobenzoates (4cyanopentanoic acid dithiobenzoate: CPADB, 2-cyano-2-propyl www.advancedsciencenews.com www.advtheorysimul.com Scheme 1. [16,[24][25][26][27][28] As specific examples, considering the activity of PheoA (Figure 1a) and ZnTPP (Figure 1b) with respect to a set of six RAFT agents which comprises dithiobenzoates (4cyanopentanoic acid dithiobenzoate: CPADB, 2-cyano-2-propyl www.advancedsciencenews.com www.advtheorysimul.com Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…Fort his experiment, aL IVE/DEAD BacLight bacterial viability kit [15] that consists of green fluorescing SYTO 9a nd red fluorescent propidium iodide (PI) was employed to differentiate S. oneidensis MR-1 cells with membranes (live cells) from those with compromised membranes (dead cells). [16,17] Then, we investigated the morphology of PPy-coated S. oneidensis MR-1 by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Such results were also approximate to that of unmodified S. oneidensis MR-1 (Figure 1b and Figure S1b), which confirmed that the viability of S. oneidensis MR-1 cells was essentially unchanged by the application of PPy coatings.T he proliferation of PPycoated bacterial cells was confirmed by cell-culture experi-ments ( Figure S2).…”
mentioning
confidence: 99%